2022
DOI: 10.1007/s00192-022-05218-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing comprehension of online information in the United States for third-line treatment of overactive bladder

Abstract: Introduction and hypothesisOveractive bladder (OAB) affects up to 43% of women. Treatment ranges from lifestyle modification to invasive therapies. Nearly 75% of patients report using the internet to gain health information creating a need for interpretable, online resources. This study is aimed at evaluating the readability of online resources for OAB treatment in the US population. Methods Google and Bing were queried regarding "sacral neuromodulation," "peripheral tibial nerve stimulation (PTNS)," and "blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Numerous studies have been published assessing the readability of patient education materials, with a staggering trend towards texts written above the recommended grade level. [11][12][13][14][15][16][17][18][19][20][21][22] Our online queries yielded an average readability level that greatly surpassed the recommended 6th grade reading level set by the NIH and the AMA. Among the four different readability formulas, the lowest average readability level was equivalent to an 11th grade reading level.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Numerous studies have been published assessing the readability of patient education materials, with a staggering trend towards texts written above the recommended grade level. [11][12][13][14][15][16][17][18][19][20][21][22] Our online queries yielded an average readability level that greatly surpassed the recommended 6th grade reading level set by the NIH and the AMA. Among the four different readability formulas, the lowest average readability level was equivalent to an 11th grade reading level.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 78%
“…Although a few patterns have been published regarding the difficult readability of non-profit websites, when examining the multitude of readability analyses, no clear trend emerges. [11][12][13][14][15][16][17][18][19][20][21][22] The Urology Care Foundation, a non-profit webpage, stands out as one of the lowest scored pages and thus was easily comprehensible. In a similar study, Routh et al compared internet sources between common and uncommon pediatric urology topics and found that webpages on uncommon topics like exstrophy had inferior accuracy and completeness.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…Indeed, this challenge is not unique to the information on CBE nor that of urology, it is endemic to all fields of medicine. Countless studies have been published evaluating the readability of patient education materials online across multiple specialties, and the trend for information to be above the recommended reading level is overwhelming (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…The first 20 results available for each country were collected for each search term (n = 20 chronic pain , n = 20 persistent pain ) as the first 20 results receive the most traffic, and this number is commonly used. 21 , 42 …”
Section: Methodsmentioning
confidence: 99%
“…The first 20 results available for each country were collected for each search term (n 5 20 chronic pain, n 5 20 persistent pain) as the first 20 results receive the most traffic, and this number is commonly used. 21,42 Two reviewers then independently read and filtered the sources through the inclusion and exclusion criteria described above. The same search methodology was used to assess government health websites for each country.…”
Section: Search Strategymentioning
confidence: 99%